2019
DOI: 10.1186/s12947-019-0162-2
|View full text |Cite
|
Sign up to set email alerts
|

Intracardiac echocardiography versus fluoroscopy for endovascular and endocardial catheter navigation during cryo-ablation of the slow pathway in AVNRT patients

Abstract: Background A new zero-fluoroscopy technique for electrophysiology catheter navigation relying on intracardiac echocardiography (ICE) has been recently reported (Ice&ICE trial). We investigated potential differences in efficacy, safety or procedural performance between conventional fluoroscopy- and ICE-guided cryothermal ablation (CA) in symptomatic AVNRT patients. Methods Clinical and electrophysiological data of AVNRT patients included in the Ice&ICE trial (22 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Examples include: recognition of important anatomical variations, control of catheter tip orientation, control of catheter-tissue contact, and early recognition of complications such as pericardial effusion and procedure-related thrombi [ 23 , 31 ]. There are scarce data on improved results of ablation in ICE-guided AVNRT procedures [ 34 , 35 ]. However, we find ICE to be a valuable tool in small children with a smallish Koch triangle, when precise positioning of the catheter on the ablation spot is of great value for successful ablation and complication avoidance.…”
Section: Discussionmentioning
confidence: 99%
“…Examples include: recognition of important anatomical variations, control of catheter tip orientation, control of catheter-tissue contact, and early recognition of complications such as pericardial effusion and procedure-related thrombi [ 23 , 31 ]. There are scarce data on improved results of ablation in ICE-guided AVNRT procedures [ 34 , 35 ]. However, we find ICE to be a valuable tool in small children with a smallish Koch triangle, when precise positioning of the catheter on the ablation spot is of great value for successful ablation and complication avoidance.…”
Section: Discussionmentioning
confidence: 99%
“…Previously studies reported on the advantage of mechanical radial ICEimaging for SP ablation [18,19]. Most recently, data from a retrospective analysis of 47 patients who underwent ICE vs. fluoroscopy-guided SP cryoablation showed that the use of ICE shortens the cryo-application duration; however, time needed for catheter placement is longer, when compared with conventional fluoroscopic guidance [20].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the “Ice and ICE” study looked at the safety and efficacy of conventional fluoroscopy-guided cryoablation with ICE-guided cryoablation of AV-nodal re-entrant tachycardia (AVNRT) [ 33 •]. In this small retrospective comparative study, all patients (22 in ICE arm and 25 in fluoroscopy arm) had successful modification of the slow pathway with similar overall procedure times without major complication events reported.…”
Section: Discussionmentioning
confidence: 99%